1994
DOI: 10.1111/j.1365-2648.1994.tb01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Rotter scale of internal‐external locus of control to determine differences between smokers, non‐smokers and ex‐smokers in their general locus of control

Abstract: Application of the Rotter scale of internal-external locus of control to determine differences between smokers, non-smokers and ex-smokers in their general locus of control This paper will relate to empirical research undertaken whilst studying for BA(Hons) in Applied Social Studies by Independent Study. The researchers are both nurses, and colleagues were among the participating subjects. The research took the form of applying the Rotter (1966) scale for internal versus external locus of control to three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Individuals with an internal LOC may be less likely to smoke (3), more likely to have had a recent pap smear or breast exam (1,8), and less likely to experience a future decline in functional status (9). However, studies have also reported that LOC is not predictive or is only weakly predictive of health behaviors (2,(5)(6)(7).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Individuals with an internal LOC may be less likely to smoke (3), more likely to have had a recent pap smear or breast exam (1,8), and less likely to experience a future decline in functional status (9). However, studies have also reported that LOC is not predictive or is only weakly predictive of health behaviors (2,(5)(6)(7).…”
mentioning
confidence: 90%
“…T he extent to which an individual perceives life events to be within his or her own control, termed locus of control (LOC), has been examined as a potential correlate of health behaviors (1)(2)(3)(4)(5)(6)(7)(8). Individuals with an external LOC are more likely to believe that life events are determined by chance, other individuals, or other outside factors, but those with an internal LOC believe they have more control over what happens to them.…”
mentioning
confidence: 99%